Beyond Inclusion: Teachers’ Creative Strategies for Building Meaningful Interactions Among Young Children - Khoirotin; Bahtiar Arbi; Khamim Zarkasih Putro (JOYCED: Journal of Early Childhood Education, 2026)
Purpose – This study aims to examine the importance of teachers’ creative strategies in fostering inclusive interactions to cultivate a sense of belonging among young children. The study was motivated by the fact that some children still do not feel fully accepted in inclusive classrooms, necessitating an approach that goes beyond merely applying the principles of inclusion namely, through teachers’ creativity in responding to children’s diversity. Design/methods/approach – This study employs a qualitative approach using a case study design conducted at the Srawung Bocah Inclusive Kindergarten in Yogyakarta. Data were collected through observation, in-depth interviews with teachers, and documentation. The researcher served as the primary instrument in observing interactions that occurred naturally. Data analysis was conducted using the Miles and Huberman model, which includes data condensation, data presentation, and drawing conclusions, with validity testing through triangulation techniques. Findings –The results of the study indicate that teachers implement creative strategies through adaptive communication, the use of varied learning media, and a flexible, child-centered learning approach. These strategies foster inclusive interactions characterized by a warm, responsive, and participatory atmosphere. Research implications/limitations – As a result, children demonstrate a sense of belonging through increased self-confidence, emotional comfort, and active engagement in activities. This study is limited to a single location, so its findings cannot yet be widely generalized. Additionally, the qualitative approach emphasizes data depth over breadth. Originality/value – This study contributes to the field of early childhood education by linking teacher creativity and inclusive interactions through the Rhodes 4P framework, and offers practical implications for the development of more inclusive and responsive learning.